Immunohistochemical evidence of leptin and its receptor in the carpal glands of domestic pigs and wild boar. Issue 1 (8th October 2014) - Dall'Aglio, Cecilia; Mercati, Francesca; Pascucci, Luisa; Bazzucchi, Cinzia; Ceccarelli, Piero
<x xml:space="preserve">Abstract</x> Background In recent years, the protein hormone leptin has been the subject of numerous studies designed to clarify and interpret its functional significance; it has been speculated that this goes well beyond the control of appetite and energy metabolism. In particular, the presence of leptin and its receptor has been observed in various glands anatomically and functionally related to the reproductive apparatus. This has led to the hypothesis that leptin may act directly in the functional control of these glands and, in general, the control of reproductive function. Hypothesis/Objectives The presence and distribution of leptin and its receptor in the carpal glands of domestic pigs and wild boar are examined, using immunohistochemical techniques. Animals Tissue samples were collected from five domestic pigs and five wild boar, following slaughter. Results The presence of leptin and its receptor was demonstrated in the glands, localized in the dark cells of the glandular secretory epithelium. In addition, no difference was observed between wild boar and domestic pigs. Conclusions and clinical importance We hypothesize that leptin may be produced by the carpal gland and may act on the gland's secretory epithelial cells with an autocrine/paracrine mechanism, thus affecting the secretory activity of the gland itself.